2022
DOI: 10.1002/jpln.202100311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen fertilization on central tendency and spatial heterogeneity of soil moisture, pH and dissolved organic carbon and nitrogen in two bioenergy croplands#

Abstract: Background Soil moisture, pH, dissolved organic carbon and nitrogen (DOC, DON) are important soil biogeochemical properties in switchgrass (SG) and gamagrass (GG) croplands. Yet their spatiotemporal patterns under nitrogen (N) fertilization have not been studied. Aims The objective of this study is to investigate the main and interactive effects of N fertilization and bioenergy crop type on central tendencies and spatial heterogeneity of soil moisture, pH, DOC and DON. Methods Based on a 3‐year long fertilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…Previous studies reported that soil DOM (including DOC and DON) concentration could be changed by N addition (Jing et al, 2021; Lei et al, 2017; Yuan et al, 2022). However, soil DOM concentration influenced by N addition remained inconsistent, with not only the magnitude but also the direction (Jing et al, 2021; Wang et al, 2022; Yuan et al, 2020). Soil DOC concentration showed increase (Niu et al, 2021; Sun et al, 2015), decrease (Jing et al, 2021; Yuan et al, 2022), and minor change (Chen et al, 2022; Li et al, 2019b) in response to N addition.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that soil DOM (including DOC and DON) concentration could be changed by N addition (Jing et al, 2021; Lei et al, 2017; Yuan et al, 2022). However, soil DOM concentration influenced by N addition remained inconsistent, with not only the magnitude but also the direction (Jing et al, 2021; Wang et al, 2022; Yuan et al, 2020). Soil DOC concentration showed increase (Niu et al, 2021; Sun et al, 2015), decrease (Jing et al, 2021; Yuan et al, 2022), and minor change (Chen et al, 2022; Li et al, 2019b) in response to N addition.…”
Section: Introductionmentioning
confidence: 99%
“…Responses of both soil respiration and DOC leaching have been shown to depend on the level of N addition (Evans et al., 2008; Peng et al., 2017; X. Wang et al., 2022) and the duration of N addition (Zhou et al., 2014). In particular in N‐limited forest ecosystems, the effects of N addition might be diminished gradually under chronic N addition (Janssens et al., 2010) and it is an open question how long the effects would be sustained.…”
Section: Introductionmentioning
confidence: 99%
“…Responses of both soil respiration and DOC leaching have been shown to depend on the level of N addition (Evans et al, 2008;Peng et al, 2017;X. Wang et al, 2022) and the duration of N addition (Zhou et al, 2014).…”
mentioning
confidence: 99%